Peningkatan Nilai Tambah Budidaya Jamur Tiram Pada Usaha Petani Semesta Jamur di Cempaka (Membuat Olahan Jamur Tiram Menjadi Bakso) - Ambarwati, Riris; Firdaus, Firdaus; Herawati, Ana Sofia; Lusiana, Herlina; Fajrianti, Illisa; Mursanto, Mursanto (Penerbit Widina, Widina Media Utama, 2024)
Oyster mushrooms are a type of woody mushroom that has a higher nutritional content compared to other types of woody mushrooms. Some nutrients contained in oyster mushrooms, such as protein, fat, phosphorus, iron, thiamin, and riboflavin, are higher than other types of mushrooms, and contain 18 types of amino acids needed by the human body without containing cholesterol (Djarijah, 2001). Although rich in nutrients, oyster mushrooms have a relatively short shelf life. This causes the selling price of oyster mushrooms to tend to be low if not sold immediately. Gunung Kupang Village is a transmigration village from the island of Java where the majority of the people who live there or their ancestors come from Java, where their descendants were born as banjar people of South Kalimantan. In Gunung Kupang village, it is located in the RT area. The results of our survey and research found that there is an oyster mushroom MSME entrepreneur “UD Jamur Semesta” where the business was formed in groups. After the formation of the group, each member decided to develop their respective oyster mushroom cultivation with individual businesses. UD Jamur Semesta has 8 employees, all of whom are family members who can still be productive together to run their business. However, the business has not been maximized in its sales, which still receives orders from word of mouth, local residents who buy at home and packaging is still using ordinary plastic, purchase of at least 1 kg. And there is no processing that makes added value for universal mushroom farmers. This Community Service activity is at the Mushroom Universe Farmer business, in Gunung Kupang Village, Cempaka District, Banjarbaru City. The purpose of this activity is to increase knowledge in the human resources of the universe farmer business, in terms of oyster needles and their benefits and being able to become one of the business ideas and increase the added value of oyster mushroom cultivation (making processed oyster mushrooms into meatballs).ABSTRAKJamur tiram merupakan jenis jamur kayu yang memiliki kandungan nutrisi lebih tinggi dibandingkan dengan jenis jamur kayu lainnya. Beberapa nutrisi yang terkandung dalam jamur tiram, seperti protein, lemak, fosfor, besi, thiamin, dan riboflavin, lebih tinggi dibandingkan dengan jenis jamur lainnya, serta mengandung 18 jenis asam amino yang diperlukan oleh tubuh manusia tanpa mengandung kolesterol (Djarijah, 2001). Meskipun kaya akan kandungan gizi, jamur tiram memiliki masa simpan yang relatif singkat. Hal ini menyebabkan harga jual jamur tiram cenderung rendah jika tidak segera terjual. Desa Gunung Kupang adalah desa transmigrasi dari pulau jawa dimana mayoritas yang tinggal disana masyarakatnya atau nenek moyangnya berasal dari jawa, dimana keturunannya lahir sebagai orang banjar kalsel. Di desa gunung kupang letaknya di wilayah RT. 30 hasil survei dan research kami menemukan ada pengusaha UMKM Jamur tiram “UD Jamur Semesta” dimana yang diawali terbentuk usahanya berkelompok. Setelah terbentuknya kelompok dari setiap anggota memutuskan untuk mengembangkan budidaya jamur tiramnya masing-masing dengan usaha perorangan. UD Jamur Semesta mempunyai 8 karyawan dimana dari 8 orang pekerja tersebut semua dari anggota keluarga yang masih bisa produktif bersama-sama untuk menjalankan usahanya. Namun usaha tersebut belum maksimal dalam penjualannya, yaitu masih menerima pesanan dari mulut ke mulut, warga sekitar yang membeli ke rumah dan pembungkusan kemasan masih menggunakan plastik biasa, pembelian minimal 1 kg. Dan belum ada pengolahan yang menjadikan nilai tambah bagi petani semesta jamur. Kegiatan Pengabdian Kepada Masyarakat ini adalah pada usaha Petani Semesta Jamur, di Desa Gunung Kupang, Kecamatan Cempaka, Kota Banjarbaru. Tujuan dari kegiatan ini adalah bertambahnya pengetahuan pada SDM usaha petani semesta, dalam mengenai jarum tiram dan manfaatnya serta mampu menjadi salah satu ide usaha dan meningkatkan nilai tambah budi daya jamur tiram (membuat olahan jamur tiram menjadi bakso).